2022
DOI: 10.1111/cch.12997
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term neurodevelopmental outcomes in very low birth weight infants with and without patent ductus arteriosus: A retrospective case control observational study

Abstract: Background: Patent ductus arteriosus (PDA) has been associated with early morbidities and long-term developmental problems in very preterm infants. Aims:The aim of this study is to investigate the effect of patent ductus arteriosus and medical treatment on long-term developmental outcomes in very low birth weight infants.Study design: This is a retrospective case control observational study. Subject:The study included preterm infants who were born before 30 weeks' gestation and birth weight less than 1,500 g a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The UK was the only country that showed an abate trend. [18] All five countries in Southern Europe showed high LBW rates. France was the only one not showing elevated tendency.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The UK was the only country that showed an abate trend. [18] All five countries in Southern Europe showed high LBW rates. France was the only one not showing elevated tendency.…”
Section: Resultsmentioning
confidence: 97%
“…Usually, ductus arteriosus shuts within two days of birth due to oxygen-induced constriction in full-term babies. About 80% of deficient birth weight babies have PDA (Patent Ductus Arteriosus) [18]. Still another important factor leading to morbidity and mortality in low-birthweight babies is infection.…”
Section: Risk Factors Associated With Very Low Birth Weight: a System...mentioning
confidence: 99%
“…Since there are a few publications from Turkey about NDD in patients with CHD ( 26 30 ), the other aim of the study is to raise awareness that NDD is a very common and masked comorbidity in patients who have undergone congenital heart surgery. Another subject we want to point out is that the ASQ-3 test is handy and feasible for ND assessment as a first step.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Elbayiyev at al. found no association between hsPDA and poor neurodevelopmental outcomes, in a retrospective case control observational cohort ( 31 ). On the other hand, in a retrospective cohort of preterm infants born <29 weeks’ gestation, Janz-Robinson et al suggested unfavorable neurodevelopmental course at 2–3 years of age, possibly related to PDA ( 32 ).…”
Section: Why Should We Worry About Patent Ductus Arteriosus In Preter...mentioning
confidence: 92%